2007
DOI: 10.1200/jco.2007.11.8109
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Double-Blind, Placebo-Controlled Study of Thalidomide in Extensive-Disease Small-Cell Lung Cancer After Response to Chemotherapy: An Intergroup Study FNCLCC cleo04–IFCT 00-01

Abstract: Treatment with thalidomide was not associated with a significant improvement in survival of SCLC patients. There was pronounced heterogeneity in survival outcomes between groups of patients. Some benefit was observed among patients with a PS of 1 or 2 (exploratory analyses), deserving further studies targeting angiogenesis in this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(68 citation statements)
references
References 26 publications
1
63
1
3
Order By: Relevance
“…However, two large randomised phase III trials failed to show a significant benefit of thalidomide in the treatment of SCLC [106,113].…”
Section: Targeted Therapiesmentioning
confidence: 99%
“…However, two large randomised phase III trials failed to show a significant benefit of thalidomide in the treatment of SCLC [106,113].…”
Section: Targeted Therapiesmentioning
confidence: 99%
“…In a phase III study, which was stopped early due to poor accrual, 92 ES SCLC patients with chemotherapy responsive disease were randomized to receive cisplatin, etoposide, epirubicin and cyclophosphamide, with or without thalidomide. Despite the small size of the study, a statistically significant difference in survival was observed in favor of the thalidomide arm: 11.7 versus 8.7 months (hazard ratio: 0.48; 95% confidence interval: 0.24-0.93; p = 0.03) [44]. More patients on the thalidomide treatment arm withdrew from the study due to toxicity (33% versus 19%), notably neuropathy and constipation.…”
Section: Basic Fibroblast Growth Factormentioning
confidence: 83%
“…In a French phase III randomized controlled trial by Pujol et al (56), 119 patients with ED-SCLC were treated with 2 cycles of PCDE (cisplatin/cyclophosphamide/ epidoxorubicin/etoposide). Those who achieved an objective response (97 patients) were randomly assigned to receive 4 additional cycles of PCDE plus oral thalidomide 400 mg/d or placebo.…”
Section: Thalidomidementioning
confidence: 99%